KUALITAS PELAYANANPROGRAM PENDAFTARAN DARING (TARINGDUKCAPIL) PADA DlNAS KEPENDUDUKAN DAN PENCATATAN SlPIL KOTA DENPASAR - Prameswari, Miralda Regina; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2021)
The Population and Civil Registration Office of Denpasar City is the main service in conducting the administrative process. Seeing this, the Department of Population and Civil Registration issued a public service innovation called TaringdukcapilProgram , which in this program is done registration through the website for various needs of population files and civil registration so that the public can do remote file creation. This study uses descriptive qualitative method with data collection techniques in the form of observation, interview and documentation studies. Based on the study of Service Quality Theory according to Zeithami-Parasuraman-Berry obtained that the quality of this program has been running well but still not optimal such as Tangibles , Reliability , Responsive , Assurance and Empathy deficiencies occur due to the lack of checking of devices to be used, socialization, knowledge of officers to the program, the public still difficulty in obtaining queue numbersTaringdukcapil Program. Keywords : Quality of Service, Program Innovation, Taringdukcapil